Association of Epstein Barr virus deoxyribonucleic acid with lung carcinoma - Amir Hossein Jafarian; Abbsali Omidi-Ashrafi; Nema Mohamadian-Roshan; Mahdi Karimi-Shahri; Kiarash Ghazvini; Samaneh Boroumand-Noughabi (Wolters Kluwer Medknow Publications, 2013)
Context: Lung cancer is the leading cause of cancer death worldwide. In addition to smoking, a variety of other contributing factors, including viral infection, have been suggested in tumorigenesis. Epstein Barr virus (EBV), which is linked to various malignancies, seems to be a good candidate. Aims: The aim of this study was to investigate the association of EBV with lung carcinomas. Settings and Design: A total number of 90 formalin fixed paraffin embedded lung tissue samples including 48 cases of lung cancers (18 squamous cell carcinomas [SCCs], 18 adenocarcinomas and 12 small cell carcinomas) and 42 non-tumoral samples (control group), were retrieved from the pathology archive. Materials and Methods: Following deoxyribonucleic acid extraction, polymerase chain reaction (PCR) was performed using an EBV-Eph PCR kit. The positive cases were studied immunohistochemically for the expression of EBV-late membrane protein-1 (EBV-LMP-1) in tumoral tissues. Statistical Analysis Used: The t-test and Fisher exact test were used and P < 0.05 was considered statistically significant. Results: Five of our cases, including four SCCs and one adenocarcinoma and two control samples showed a positive reaction in PCR. All positive tumoral cases showed diffuse staining with LMP-1 in immunohistochemistry. Conclusions: We found a significant difference in the presence of the EBV genome in cases of lung SCC compared to other lung lesions (P = 0.02). According to our data, EBV is not at major play in the non-lymphoepithelioma-like cancers of the lung in general, but may have a role in the tumorigenesis of some lung SCCs.